Cultural Competency Education in Pharmacy Curricula-Need and Implementation - Patel, Isha; Gadwal, Thanveer; Shrestha, Shameen; Khieri, Shiama; Miller, Mary Kate; Guy, Jason W; Chang, Jongwha; Johnson, Mark (Indian Journal of Pharmacy Practice)
Cultural competency is the ability to interact effectively with people of different cultures. Development of cultural competency skills among health professions students has been a challenge to integrate into curricula. However, further integration of cultural competency concepts may be needed in the future as some literature has shown that training in this area can lead to benefits in patient outcomes. To date there have been different methodologies used to enhance cultural competency including didactic training, community engagement and experiential models focused on communication. The Substance Abuse and Mental Health Services Administration has also provided a multi-step plan to help in advancing health professionals’ skills in the area of cultural competency. In addition, the Accreditation Council for Pharmacy Education has made cultural competency a major standard for pharmacy programs, thus further integration of valuable instructional methods for cultural competency are needed. Other professional organizations have also started to develop tools and resources to help educate individuals in the area of cultural competency. In the future, further integration of cultural competency education will be necessary to comply with accreditation standards and to improve health professionals’ skillset, which may in turn result in improved patient outcomes.
Keywords: Cultural competency; United States; Curriculum; Education; Healthcare.